Concept of Purity in the Studies of the Indian Caste System - Mickevičienė, Diana (Acta Orientalia Vilnensia, 2003)
The preoccupation of Hindus with their ritual purity was always noticed and observed by the visitors of India from the early days. This was also noted by the anthropologists studying India in the beginning of the 20th century (e.g. Bouglé in 1908). However no in-depth assessment of its implications on the essential social structure of India - caste system - was given in social anthropology until Louis Dumont formulated his landmark theory of the analysis of the Indian caste system in his Homo Hierarchicus (1966).It was Dumont who first claimed that it was not possible to explain the nature of the caste system without establishing an essential principle permeating all the visible features of the caste system (e.g. hierarchy, separation, division of labour). He concluded that such a principle was found in Hinduism and called it a fundamental opposition between purity and pollution. This essential link between the caste system and Hinduism makes it impossible to have parallel analysis of Indian caste systems and non- Indian systems of strict social stratification which, as Dumont argued, could not and should not be called caste systems.However in this article, without taking position on whether caste system can only be found in India, or it is a more general feature of human social organization, I would like to focus on Dumont’s analysis of the concept of purity, its merits and shortcomings as well as the evolution of this concept in a post-Dumont Indian studies of social anthropology and Hindu perceptions as related to the changes in Hindu way of life. Finally, with the help of Dumont’s critics I would try to make some assumptions on the possible future transformation of the popular concept of purity, basing my premises on the secondary information I received from my fieldwork on the stability and change of the caste system as well as on my personal experience of life in India.